The influence of various South African aggregates on the creep of concrete - Mallows, Frank Arthur (Department of Civil Engineering, 2023)
The aim of this thesis is to identify which south African aggregates have an extreme effect on the creep of concrete. Eight sets of experimental data, incorporating five types of aggregate, are presented. Further secondary effects have also been identified from the experimental results. These include Admixtures, Eastern Province Cement and Heat-curing. A computer program, CONVERS3, was developed in order to convert experimental results from the form of specific creep to that of creep factor, thereby making the data more accessible for comparison purposes. In order to allow for variation in cement content and age of loading, between the different test series, the partial coefficients from the CEB 1970 code recommendations were incorporated in the program. Once these variations had been allowed for, the results from the various test series were then compared in order to identify the secondary effects of Aggregate Type, Admixture, Cement Type and Heat-curing. The comparison of the test data is presented in two forms, namely, creep factor against time plots, and 300-day creep factor values. The latter were obtained by fitting a hyperbolic curve to the experimental data and thereby interpolating a value at 300 days. By comparing the experimental data, it was found that the use of an Eastern Province Ordinary Portland Cement, and the use of a P4 Admixture, both caused a 25% increase in the resulting creep factor. From the aggregates decreasing sandstone, comparisons that were made, it was found that the affected the creep of concrete in the following order of influence: Eastern Province Quartzitic Reef Quartzite, Hornfels, Granite and Dolerite.